A Decade of Solid Oxide Electrolysis Improvements at DTU Energy. (11th January 2017) - Hauch, Anne; Brodersen, Karen; Chen, Ming; Graves, Christopher; Jensen, Søren Højgaard; Jørgensen, Peter Stanley; Hendriksen, Peter Vang; Mogensen, Mogens Bjerg; Ovtar, Simona; Sun, Xiufu
Abstract : Solid oxide electrolysis cells (SOECs) can efficiently convert electrical energy (e.g. surplus wind power) to energy stored in fuels such as hydrogen or other synthetic fuels. Performance and durability of the SOEC has increased orders of magnitudes within the last decade. This paper presents a short review of the R&D work on SOEC single cells conducted at DTU Energy from 2005 to 2015. The SOEC improvements have involved increasing the of the oxygen electrode performance, elimination of impurities in the feed streams, optimization of processing routes, and fuel electrode structure optimization. All together, these improvements have led to a decrease in long-term degradation rate from 40 %/kh to 0.4 %/kh for steam electrolysis at -1 A/cm 2, while the initial area specific resistance has been decreased from 0.44 Wcm 2 to 0.15 Wcm 2 at -0.5 A/cm 2 and 750 °C.